PELAKSANAAN PENGANGKATAN ANAK BERDASARKAN PERATURAN PEMERINTAH NOMOR 54 TAHUN 2007 TENTANG PELAKSANAAN PENGANGKATAN ANAK DI PANTI ASUHAN PUTERI AISYIAH MUHAMMDIYAH KOTA PEKANBARU - Apriliani, Nuri; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Adoption is a legal act which distract a child from parental authority enviromental legal guardian. Adoption should be based on applicable laws and regulations, to prevent irregularities. Responsibility that needs to be awakened and nurtured by the adoptive parents to the adopted child is to maintain and raise, protect and guarantee their health, both physically and mentally from a variety of diseases that can harm him, educated him with a variety of knowledge and skills that are useful for life, happy child’s world and the here after by providing religius education in accordance with religius affiliations.There are obstacles in the process of adoptionand this is because : First, legislation based on the regulations are too complicated convolution, second, take a long time to comply with a rule of adoption through a court ruling, third, requires a lot of costs, while the orphanage did not provide a cost specifically in terms of adoption, because the orphanage more emphasizes the social function to alleviate children with social problems.